2022
DOI: 10.1186/s13023-021-02167-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the frequency of causal genetic variants in foetuses with congenital heart defects: a Chinese cohort study

Abstract: Background The belief that genetics plays a major role in the pathogenesis of congenital heart defects (CHD) has grown popular among clinicians. Although some studies have focused on the genetic testing of foetuses with CHD in China, the genotype–phenotype relationship has not yet been fully established, and hotspot copy number variations (CNVs) related to CHD in the Chinese population are still unclear. This cohort study aimed to assess the prevalence of chromosomal abnormalities in Chinese fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Corresponding authors for 18 of the original 52 papers were emailed for further information where this was incomplete and four of these responded with complete data for inclusion, of which one was excluded as it had less than 20 cases 19–22 . This left 21 studies included in the final meta‐analysis (incorporating 1957 cases) 19–21,23–40 . Of the 21 studies in this paper, 8 were used in the previous analysis by Mone, et al 10 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corresponding authors for 18 of the original 52 papers were emailed for further information where this was incomplete and four of these responded with complete data for inclusion, of which one was excluded as it had less than 20 cases 19–22 . This left 21 studies included in the final meta‐analysis (incorporating 1957 cases) 19–21,23–40 . Of the 21 studies in this paper, 8 were used in the previous analysis by Mone, et al 10 .…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21][22] This left 21 studies included in the final metaanalysis (incorporating 1957 cases). [19][20][21][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Of the 21 studies in this paper, 8 were used in the previous analysis by Mone, et al 10 Table S1 outlines the study characteristics. Supplementary Figure S1 demonstrates the quality assessment.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…This study summarizes the reported ultrasound phenotypes of fetuses with the 17q12 microduplication syndrome ( Table 2 ). Lu et al reported that the 17q12 microduplication was associated with congenital heart defects ( 21 ). However, no ultrasound phenotype of congenital heart defects was found in our study.…”
Section: Discussionmentioning
confidence: 99%